Social value, educational qualification and campaign strategy of Sangguniang Bayan members preferred by voters in Dingle, Iloilo. - Pacaco, Robert
This study determines the social value, educational qualifications and campaign strategy of the Sanggunian Bayan members preferred by voters. This research endeavor also determines whether age, sex, family, income, and educational qualification have something to do with preference of social value, educational qualification and campaign strategy of the Sangguniang Bayan members., In the undertaking of the study, the researcher used slovin's formula to get the sample size. Chi-square test was used to determine whether voters' preference are independent of their age, sex, family income and educational qualification. The major findings of teh study are, 1) voter's prefer marunong makisama as social value of their Sangguniang Bayan members, 2) voters prefer their Sangguniang Bayan member to be college graduates, 3) voter's prefer caucus/ rally as the campaign strategy used by their Sangguniang Bayan members. There are other significant propositions and valuable insights this study has yielded. This research concludes the following: 1)preference of the social value is dependent on the voters' age, 2) preference of educational qualification is independent on voters' age, 3) preference on campaign strategy is independent of the voters' age, 4) preference of the social value is independent on the voters' sex, 5) preference of educational qualification is independent of the voters' sex, 6) preference of the campaign strategy is independent of the voters' sex, 7) preference of the social value is dependent of the voters' family income, 8) preference of the educational qualification is dependent of the voters' family income. 9) preference of the campaign strategy is independent of the voters' family income, 10) preference of the social value is independent of the voters' educational qualification, 11)preference of the educational qualification is independent of the voters' educational qualification, 12) preference of the campaign strategy is independent of the voters' educational qualification.